Impact of Area Under the Concentration-Time Curve-Guided Monitoring on Vancomycin Nephrotoxicity and Treatment Outcomes in Methicillin-Resistant Staphylococcus Aureus Bacteremia in Korean Patients - Young Rong Kim, MD; Ha-Jin Chun; Jung Yeon Heo, MD, PhD; Jin Sae Yoo, MD; Young Hwa Choi, MD, PhD; Eun Jin Kim, MD (Elsevier, 2022)
Background: Current guidelines for the therapeutic monitoring of vancomycin recommend dosing based on the area under the concentration-time curve (AUC) to achieve clinical efficacy while reducing nephrotoxicity. Although a wide range of nephrotoxicity thresholds have been reported, few studies have documented clinical outcomes based on AUC-guided vancomycin dosing in Korea. Objective: The aim of the study was to evaluate whether a relationship exists between AUC and treatment outcomes in vancomycin treated patients in methicillin-resistant Staphylococcus aureus bacteremia. Furthermore, this study tries to estimate AUC threshold for treatment failure and nephrotoxicity. Methods: The records of adult patients with methicillin-resistant Staphylococcus aureus bacteremia treated with vancomycin for ≥72 hours without dialysis between April 2013 and April 2021, were reviewed retrospectively. Treatment success was defined as defervescence and blood culture sterilization by day 7. Nephrotoxicity was defined as an increase in serum creatinine levels ≥0.3 mg/dL or a 50% increase from baseline on 2 consecutive days. Bayesian estimation was used to predict individual vancomycin AUC. Both classification and regression tree and receiver operating characteristic curve analyses were performed to estimate the optimal AUC thresholds for vancomycin efficacy and nephrotoxicity. Results: Of 118 patients, 61 (51.7%) experienced treatment failure and 42 (35.6%) developed acute kidney injury. The vancomycin AUC threshold for predicting acute kidney injury was 615.0 mg· hr/L. In the multivariate analysis, AUC ≥615.0 mg· hr/L was a significant risk factor for nephrotoxicity (adjusted odds ratio [aOR] = 5.24; 95% CI, 1.8-14.65). The lower threshold for treatment failure was not defined because it was not statistically significant. Risk factors for treatment failure included low body mass index (aOR = 0.82; 95% CI, 0.70-0.96), severity of acute illness represented by complicated infection (aOR = 77.56; 95% CI, 16.7-359.4) and comorbidities, such as solid organ tumors (aOR = 6.61; 95% CI, 1.19-36.81) and cerebrovascular disease (aOR = 6.05; 95% CI, 1.17-31.23). Conclusions: Although AUC-guided vancomycin dosing was associated with a reduced risk of acute kidney injury, its ability to predict clinical outcomes was modest. Further studies are needed to define the AUC therapeutic range to maximize efficacy and minimize nephrotoxicity. (Curr Ther Res Clin Exp. 2023; 83:XXX-XXX)